2018
DOI: 10.1089/gtmb.2017.0204
|View full text |Cite
|
Sign up to set email alerts
|

Replication Study Confirms the Association of the Common rs1800629 Variant of the TNFα Gene with Postmenopausal Osteoporosis Susceptibility in the Han Chinese Population

Abstract: We have shown that a TNFα gene polymorphism, rs1800629, is highly significantly associated with postmenopausal osteoporosis and BMD in the female Han Chinese population. Additional sequencing-based studies are needed to investigate the genetic architecture of this genomic region and its relationship with osteoporosis-related phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Therefore, the exact underlying mechanisms of how this SNP affects the expression of TNF‐α and hence affects development of osteoporosis are still unclear and further functional investigation is needed to clarify these issues. Additionally, it should be noted that several included studies reported inconsistent findings for the effect of G308A polymorphism on osteoporosis . The reason might be ascribed to the ethnic differences of each study.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Therefore, the exact underlying mechanisms of how this SNP affects the expression of TNF‐α and hence affects development of osteoporosis are still unclear and further functional investigation is needed to clarify these issues. Additionally, it should be noted that several included studies reported inconsistent findings for the effect of G308A polymorphism on osteoporosis . The reason might be ascribed to the ethnic differences of each study.…”
Section: Discussionmentioning
confidence: 95%
“…Nine studies evaluated the associations between TNF-α G308A polymorphism (GG vs GA+AA) and BMD, in which eight studies focused on LS-BMD [9][10][11][12]15,16,19,21 and six studies focused on FN-BMD [10][11][12][13]15,16 (Figure 3). According to the results, the mutant genotypes did not significantly affect the BMD as compared with GG genotype based on either LS-BMD data (P = 0.55, I 2 = 60%) or FN-BMD data (P = 0.37, I 2 = 91%).…”
Section: Gg Vs Ga+aamentioning
confidence: 99%
See 3 more Smart Citations